Locally Administered Photodynamic Therapy for Cancer Using Nano-Adhesive Photosensitizer - Yoshiki Komatsu; Toru Yoshitomi; Van Thi Hong Doan; Hiromi Kurokawa; Saori Fujiwara; Naoki Kawazoe; Guoping Chen; Hirofumi Matsui (MDPI AG, 2023)
Photodynamic therapy (PDT) is a great potential anti-tumor therapy owing to its non-invasiveness and high spatiotemporal selectivity. However, systemically administered photosensitizers diffuse in the skin and the eyes for a long duration, which cause phototoxicity to bright light and sunlight. Therefore, following PDT, patients must avoid exposure of to light and sunlight to avoid this phototoxicity. In this study, we have developed a locally administered PDT using nano-adhesive porphyrin with polycations consisting of quaternary ammonium salt groups (aHP) as a photosensitizer. The aHP, approximately 3.0 nm in diameter, adhered the negatively charged cell membrane via electrostatic interaction. The aHP localized to the endosome via cell adhesion and induced apoptosis upon 635 nm light irradiation. On being administered subcutaneously on the tumor, 30% of the injected aHP remained in the administered sites. However, low-molecular-weight hematoporphyrin dihydrochloride (HP) disappeared due to rapid diffusion. PDT with locally administered aHP showed a higher anti-tumor effect after light irradiation at 635 nm for three days compared to low-molecular-weight HP. Intraperitoneal administration of HP caused severe phototoxicity upon irradiation with ultraviolet A at 10 J cm−2, whereas aHP did not cause phototoxicity because its diffusion into the skin could be suppressed, probably due to the high-molecular weight of aHP. Therefore, locally administered PDT with aHP is a potential PDT having high therapeutic efficacy without phototoxicity.